Lonchopteridae (Diptera) from Guangxi, Southwest China - Dong, Qibiao; Pang, Baoping; Yang, Ding (Zootaxa, 2008)
The family Lonchopteridae is recorded from Guangxi for the first time. Two genera and 6 species are recognized. Two new species, Lonchoptera pinglongshanensis Dong, Pang and Yang, sp. nov. and Lonchoptera unicolor Dong, Pang and Yang, sp. nov., are described. One species, Lonchoptera pipi Andersson, is recorded from China for the first time. A key to the species of Lonchopteridae from Guangxi is presented.